Optimization method through topology reconfiguration for mobile underwater wireless sensor networks - Ming HE; Wen-hui LIANG; Qiu-li CHEN; Xi-liang CHEN; Jian CHEN (Tongxin xuebao)
The topology of mobile underwater wireless sensor networks (MUWSN) evolves dynamically with ocean currents,which will have great impact on network performance.To solve this problem,a topology optimization method for MUWSNs is proposed based on topology reconfiguration.Firstly,the proposed method optimizes the coverage rate of MUWSNs by adjusting the location of sensor nodes through simulating fish behaviors.Secondly,to optimize the connectivity of MUWSNs,the proposed method repairs disconnected positions and eliminates key nodes in MUWSN through using redundant nodes.Finally,simulation results verify the rationality and validity of the proposed method.Experimental results show that the algorithm can guarantee the network coverage is maintained at about 97%,connectivity rate above 89%,with lower energy consumption.